Brief telephone interventions for problem gambling: a randomized controlled trial. (14th February 2018) - Abbott, Max; Hodgins, David C.; Bellringer, Maria; Vandal, Alain C.; Palmer Du Preez, Katie; Landon, Jason; Sullivan, Sean; Rodda, Simone; Feigin, Valery
Abstract: Background and aims: Problem gambling is a significant public health issue world‐wide. There is substantial investment in publicly funded intervention services, but limited evaluation of effectiveness. This study investigated three brief telephone interventions to determine whether they were more effective than standard helpline treatment in helping people to reduce gambling. Design: Randomized clinical trial. Setting: National gambling helpline in New Zealand. Participants: A total of 462 adults with problem gambling. Interventions and comparator: (1) Single motivational interview (MI), (2) single motivational interview plus cognitive–behavioural self‐help workbook (MI + W) and (3) single motivational interview plus workbook plus four booster follow‐up telephone interviews (MI + W + B). Comparator was helpline standard care [treatment as usual (TAU)]. Blinded follow‐up was at 3, 6 and 12 months. Measurements: Primary outcomes were days gambled, dollars lost per day and treatment goal success. Findings: There were no differences across treatment arms, although participants showed large reductions in gambling during the 12‐month follow‐up period [mean reduction of 5.5 days, confidence interval (CI) = 4.8, 6.2; NZ38 lost (32, 44; 80.6%), improved (77.2%, 84.0%)]. Subgroup analysis revealed improved days gambled and dollars lost for MI + W + B over MI or MI + W for a goal of reduction of gambling (versus quitting) and improvement in dollars lost by ethnicity, gambling severity and psychological distress (all P < 0.01). MI + W + B was associated with greater treatment goal success for higher gambling severity than TAU or MI at 12 months and also better for those with higher psychological distress and lower self‐efficacy to MI (all P < 0.01). TAU and MI were found to be equivalent in terms of dollars lost. Conclusions: In treatment of problem gambling in New Zealand, brief telephone interventions are associated with changes in days gambling and dollars lost similar to more intensive interventions, suggesting that more treatment is not necessarily better than less. Some client subgroups, in particular those with greater problem severity and greater distress, achieve better outcomes when they receive more intensive treatment.